Antidiabetic Activity of Catharsntus Pusillus: A Review - Asija, Rajesh; Swami, Amandeep; Singh, Ravindra (Journal of Biomedical and Pharmaceutical Research, 2023)
Native to India, Caesalpinia pulcherrima Swartz, also known as Guletura, is widely distributed in South India and is used in Indian medicine for its leaves, flowers, bark, and seeds. Numerous active elemental fractions, including flavonoids, carotenoids, glycosides, peltogynoids, phenols, sitosterol, pulcherrimin, lupeol, lupeol acetate, myricetin, quercetin, and rutin, as well as caesalpin-type diterpenoids, are present in the plant. The goal of the current study was to evaluate the anti-anxiety effects of several leaf extracts from Caesalpinia pulcherrima, including n-hexane, chloroform, ethyl acetate, and methanol, using albino mice and the elevated plus maze (EPM) model. Different dosages of the extracts (200 and 400 mg/kg) were administered orally to albino mice, and their behavior was monitored using the EPM. Standard (positive control) dosage was 2 mg/kg of benzodiazepines (P.O.). The results were similar to those of the common antianxiety medication diazepam (2 mg/kg), indicating that the methanol extract of Caesalpinia leaves demonstrated a maximum and significant dose-dependent effect on EPM at 200 and 400 mg/kg. Two distinct dosages of Caesalpinia pulcherrima (200 and 400 mg/kg) in the Actophoptometer model demonstrated a dose-dependent reduction in locomotor activity in comparison to the control animals. The presence of polyphenols in the methanol extract, as revealed by the phytochemical screening, may account for C. pulcherrima’s anxiolytic potential. Therefore, this plant may also be developed as a possible effective anti-anxiety medication. Keywords: Caesalpinia Pulcherrima, Albino Mice, Actophoptometer, Pulcherrimin, Myricetin